Pengaruh Persepsi, Motivasi, Minat, dan Pengetahuan Perpajakan Terhadap Keputusan Pemilihan Berkarir Dibidang Perpajakan - Nella Sersa Naradiasari; Djoko Wahyudi (Politeknik Ganesha Medan, 2022)
The choice of a career in taxation is a high desire based in oneself to develop special thoughts, feelings, and actions regarding a career in taxation. This is by directing themselves to a new stage in their lives, seeing their position in life making career decisions. This study aims to examine and analyze the effect of perceptions, motivations, interests, and knowledge of taxation on students' decisions to choose a career in taxation. The population used was students of accounting and management study programs at Stikubank University Semarang and Dian Nuswantoro University Semarang. The sample of this study used a purposive sampling method with the criteria of Accounting and Management students who had taken taxation courses and obtained a sample of 100 respondents. In this study, primary data is used, namely data that is collected and processed by yourself, the results are in the form of numbers listed on a questionnaire scale which are processed using SPSS. The technique used in data collection is a questionnaire questionnaire media. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that perceptions and motivations have a positive effect on student decisions to choose a career in taxation. Likewise, the variables of interest and knowledge of taxation also have a positive influence on students' decisions to choose a career in taxation. Keywords: Interests; Motivation; Tax Knowledge; Perception